The Effect of Surface Leakage Current on Frequency Domain Spectroscopy of 22 kV OIP Bushing - Rojanasunan, Warisanan; Chumpiboon, Komin; Udomluksananon, Patt; Jeenmuang, Siwakorn; Chancharoensook, Phop; Pattanadech, Norasage (My University, 2024)
In this paper the dielectric response in frequency domain or frequency domain spectroscopy (FDS) is used to assess the effect of surface leakage current both from high voltage side and ground side on the FDS results of OIP bushings. The test object in this paper is a 22 kV OIP bushing which is out of service. The surface leakage current can be simulated using the copper tape as a bandage around the bushing core in several locations. From the FDS results, several parameters i.e., dissipation factor, capacitance, and capacitance ratio together with frequency scanning of capacitance and dissipation factor from many cases were investigated to get the fundamental knowledge of how to interpret the FDS result of OIP bushing.
Keywords: condition assessment; frequency domain spectroscopy; OIP bushing; surface leakage current